2016
DOI: 10.1530/erc-16-0372
|View full text |Cite
|
Sign up to set email alerts
|

Application of molecular biology of differentiated thyroid cancer for clinical prognostication

Abstract: Although cancer outcome results from the interplay between genetics and environment, researchers are making a great effort for applying molecular biology in the prognostication of differentiated thyroid cancer (DTC). Nevertheless, role of molecular characterisation in the prognostic setting of DTC is still nebulous. Among the most common and well-characterised genetic alterations related to DTC, including mutations of BRAF and RAS and RET rearrangements, BRAF V600E is the only mutation showing unequivocal asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 152 publications
0
36
0
2
Order By: Relevance
“…The BRAF mutation, confirmed as the most common driver mutational event involved in PTC [6, 7], has been identified as a highly specific marker of thyroid cancer as the mutation occurs exclusively in thyroid malignancy rather than in benignancy [8, 9]. In addition to the BRAF mutation, point mutations of the RAS gene, including NRAS, HRAS, and KRAS isoforms [6], represent the second most common genetic alterations in PTC [10]. In recent years, studies have found that TERT promoter mutations are emerging as a feasible tool for thyroid molecular prognostication [11, 12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The BRAF mutation, confirmed as the most common driver mutational event involved in PTC [6, 7], has been identified as a highly specific marker of thyroid cancer as the mutation occurs exclusively in thyroid malignancy rather than in benignancy [8, 9]. In addition to the BRAF mutation, point mutations of the RAS gene, including NRAS, HRAS, and KRAS isoforms [6], represent the second most common genetic alterations in PTC [10]. In recent years, studies have found that TERT promoter mutations are emerging as a feasible tool for thyroid molecular prognostication [11, 12].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, studies have found that TERT promoter mutations are emerging as a feasible tool for thyroid molecular prognostication [11, 12]. Moreover, TP53 mutations may also act as a prognostic marker because it is typically considered a marker of tumor differentiation [6, 10]. In more in-depth molecular studies of PTMC, a correlation between BRAF and/or TERT promoter mutations and high-risk clinicopathological features of the lesion were described [13, 14].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, molecularly established prognostication for PTC has been broadly advised (2)(3)(4). The role of BRAF V600Emutation test in bettering the preoperative premonition of thyroid nodules US guided fine-needle aspiration (FNA) is dubious in terms of the prognostic accuracy of BRAF V600E mutations in PTC (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…When considering all age groups, average incidence of thyroid cancer is 6.5% in women and 5.4% in men [1]. In general, about 75% of malignant thyroid tumours are presented as papillary thyroid cancer and 13% as follicular thyroid cancer, while the other types of thyroid cancer occur as medullary thyroid cancer by 7-8%, and to a lesser extent, as anaplastic (undifferentiated) thyroid cancer [2]. Recently, there have been some changes in the incidence order of thyroid cancer and particularly, micropapillary variant has been started to be observed more commonly [3].…”
Section: Introductionmentioning
confidence: 99%